Prevalencia de anticuerpos contra Trypanosoma cruzi en reservorios domésticos y silvestres en Amalfi, Antioquia (2000)
ABSTRACT: The prevalence of Trypanosoma cruzi in domestic and wild reseroirs in nine localities of the Amalfi town, (Antioquia, Colombia), was determined. Blood samples were tested by hemoculture, xenodiagnosis, and thick smears to determine the percentage of Trypanosoma infection and to evaluate the presence of antibodies against the parasite in these species. Vector activity was previusly reported in households of this minicipality in 1994, followed by the confirmation of presence of the parasite in the vectors. Sixty-three samples from canines and 33 of several other wild animal species like Didelphis marsupialis, Proechymis semiespinosus, Phylander spp., Among other ere collected. The percentage of animals with antibodies against the parasite, measured by ELISA, was 47.6% for dogs and 20% for other wild animals. The parasite was isolated once from a canine blood simple and the identification confirmed by morphology and IFI. In this paper we discuss the results and we suggest the realization of additional studies regarding these aspects.